Distribution of sickness absence in the European Union countries. Issue 10 (17th September 2004) - Gimeno, D; Benavides, F G; Benach, J; Amick, B C
Abstract : Aims: To determine the sickness absence frequency in European Union (EU) countries. Methods: Sickness absence was measured by questionnaire using the Third European Survey on Working Conditions. Employees were considered to have sickness absence if they reported to be absent at least one day in the past 12 months because of an accident at work, work related problems, or by other health problems. Results: Sickness absence percentages were lower in Southern European countries compared with Central and Northern European countries, and, in general, slightly higher in men than in women. Conclusion: This is the first description of sickness absence in each of the 15 EU countries. Examination of the sickness absence patterning between EU countries could indicate countries where important lessons to reduce sickness absence are to be learned and diffused across the EU.